1989
DOI: 10.1128/jvi.63.11.4590-4602.1989
|View full text |Cite
|
Sign up to set email alerts
|

The regions important for the activator and repressor functions of herpes simplex virus type 1 alpha protein ICP27 map to the C-terminal half of the molecule

Abstract: The herpes simplex virus type 1 (HSV-1) a or immediate-early proteins ICP4 (IE175), ICPO (IE110), and ICP27 (IE63) are transacting proteins which affect HSV-1 gene expression. We previously showed that ICP27 in combination with ICP4 and ICPO could act as a repressor or an activator in transfection assays, depending on the target gene (R. E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
109
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 94 publications
11
109
0
Order By: Relevance
“…Expression of the IE63 protein was required for this virally mediated effect on 3Ј processing, and this is in accordance with previous data which demonstrated, with a range of virus mutants deficient in IE gene expression and by transient transfection studies, that this on July 10, 2020 by guest http://jvi.asm.org/ gene product was essential for upregulation of poly(A) site usage (28). Several studies have demonstrated that the IE63 protein is involved in the regulation of HSV gene expression (11,30,39,43,44) and is specifically required for late gene expression (13,39). The plethora of conflicting information and the apparently multifunctional nature of the IE63 protein have, however, made identification of the specific mechanism(s) of this regulation difficult.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Expression of the IE63 protein was required for this virally mediated effect on 3Ј processing, and this is in accordance with previous data which demonstrated, with a range of virus mutants deficient in IE gene expression and by transient transfection studies, that this on July 10, 2020 by guest http://jvi.asm.org/ gene product was essential for upregulation of poly(A) site usage (28). Several studies have demonstrated that the IE63 protein is involved in the regulation of HSV gene expression (11,30,39,43,44) and is specifically required for late gene expression (13,39). The plethora of conflicting information and the apparently multifunctional nature of the IE63 protein have, however, made identification of the specific mechanism(s) of this regulation difficult.…”
Section: Discussionsupporting
confidence: 91%
“…The 63-kDa IE protein (IE63 or ICP27) encoded by the UL54 gene (26) is a nuclear phosphoprotein and is one of two IE proteins essential for lytic virus replication. IE63 plays a key role in the switch from early to late gene expression (37,39), and this multifunctional protein has both trans-repressor and trans-activator functions (11,30,43,44). Transfection studies have demonstrated that IE63 acts synergistically with IE pro-teins IE175 and IE110 to repress expression from IE and early promoters and activate expression from late promoters (11,30,43); IE63 also affects the cellular localization of these two IE proteins (41,44).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our general approach was mutational dissection of the pro region of the TGFOI precursor to investigate the structural features that are important in posttranslational events such as proteolytic processing, disulfide bridge formation, protein secretion and latent complex formation . Linker insertional mutagenesis has been successfully used to study functional domains within the v-fps (Stone et al ., 1984), glucocorticoid receptor (Giguere et al, 1986), c-myc (Stone et al ., 1987), v-fms (Lyman et al, 1987), and HSV 1 (Hardwicke et al ., 1989) . This type of mutagenesis provides evenly distributed in-frame insertion of several amino acids throughout the protein coding region by introducing synthetic oligonucleotide linkers at specific restriction sites.…”
Section: Construction Of a Series Of Inframe Insertion And Deletion Mmentioning
confidence: 99%
“…Most attention on the 512-amino-acid IE63 protein in recent years has focused on its potential role in 3Ј mRNA and poly(A) processing, splicing, and mRNA stabilization events (43,47,58,72). Mutations involved in both the positive and negative modulatory effects of IE63 have been mapped to the Cys-rich C terminus (26,42,64), which contains one of only three small minimally conserved motifs. Recently, an unusual activator domain requiring specific conserved Cys and His residues has been mapped to this location by GAL4 fusion experiments in the varicella-zoster virus homolog (55).…”
mentioning
confidence: 99%